Konstrukcija ženskog identiteta u poeziji Tina Ujevića - Tepavčević, Miodarka (Slavia Centralis, 2020)
New readings of Ujević’s texts have made it possible to analyse the structure of the linguistic discourse about women as well as the linguistic expressions of value-based attitudes toward them. In the paper, the author deals with an analysis of female identity, which in the context of the wider discourse illuminates many details of his views towards women. With this work we would like to point out the significance and role of women in Ujević’s poetry and reveal another segment of his poetic legacy. From his earliest poetry collections and initial rhymes, to the painful verses and mature odes, Ujević’s poems are full of numerous fairies, mythological goddesses, women who were loved and those with unfulfilled dreams, who through the power of omnipresence together constitute the voice of one woman. The defining of this harmonic voice of many women appears as an indispensable part of the narrative and the carrier of the poetic message.
Keywords: Tin Ujević; Croatian literature; female identity; love